Pengendalian Kualitas dengan Metode Failure Mode and Effect Analysis (FMEA) Pada Pembongkaran Bahan Baku Impor di PT X - Wahyu Adji Sulistiyono; Joumil Aidil Saifuddin (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Industry always carries out production planning for success in various sectors and reduces the occurrence of failures, defects in the products produced and other problems in warehouses and other production areas. One of the crucial or important problems in the company is in the warehousing (warehouse), where the case study I took was 4 problems in the warehouse including full warehouse capacity, arrivals not on schedule, heavy equipment experiencing damage and differences in data in files and reality. Of these 4 problems, they will be resolved using FMEA (Failure Mode and Effect Analysis). In completing the FMEA, the final result was the largest RPN value at full warehouse capacity with the cause of the problem being limited locations that could be built with RPN 294. This led to remedial efforts to resolve the company's problems. Hopefully, with this resolution, it can help companies reduce the risk of less than optimal warehouses in the company.